第54次日本南極地域観測隊気象部門報告2013 - 安達, 正樹; アダチ, マサキ; 斉藤, 信也; サイトウ, シンヤ; 石丸, 和樹; イシマル, カズキ; 大森, 英裕; オオモリ, ヒデヒロ; 三浦, 恒人; ミウラ, ヒサト; Adachi, Masaki; Saitou, Shinya; et al. (国立極地研究所, 2020)
この報告は，第54次日本南極地域観測隊気象部門が，2013年2月1日から2014年1月31日まで昭和基地において行った気象観測結果をまとめたものである．新規に開始したS17での観測を除き，観測方法，測器，統計方法等は第53次隊とほぼ同様である．越冬期間中の特記事項としては，次のものがあげられる． 1） 3月と4月に平年より多いブリザードを記録し積雪量が増加したため，各月の月最深積雪はそれぞれ第2位と第1位を記録した．また，越冬中のブリザードも平年より多かったため，8月以降2014年1月まで月最深積雪の極値を連続して更新した． 2） 昭和基地上空のオゾン全量は，9月下旬からオゾンホールの目安となる220 m atm-cmを大きく下回ったが，9月28日以降10月中旬までは220 m atm-cmを上回ることが多くなった．11月上旬にはオゾン全量は回復した． 3） 2013年1月に，新たにロボット気象計をS17航空機観測拠点に設置し，運用を開始した．湿度データを除き，越冬期間中の観測は順調であった．また，S16ロボット気象計と比較してより安定してデータを受信することができた． This report presents meteorological observations obtained by the Meteorological Observation Team of the 54th Japanese Antarctic Research Expedition (JARE-54) at Syowa Station, Antarctica, during February 2013-January 2014. The observation methods, instruments and statistical methods used by JARE-54 were almost the same as those used by JARE-53, except for the new observation at S17. Remarkable features during the period of JARE-54 are as follows. 1） In March and April 2013, more blizzards than normal were observed and snow accumulation increased, therefore the maximum snow depth of the month updated the record ranking second place and first place, respectively. Also, for the sixth month in a row from August, the maximum snow depth of the month updated the record ranking first place because the blizzards were observed more often than normal during the period of JARE-54. 2） The amount of the total ozone over Syowa Station was considerably below 220 m atm-cm, which is a measure of the ozone hole from late September; however, it was frequently above the measure from September 28th onward to the middle of October, and recovered at the beginning of November. 3） A new radio-robot telemeteorograph was installed at S17 base near Syowa Station and brought into operations in January 2013. We got data from this telemeteorograph more steadily than from an old one at point S16. departmental bulletin paper